EVALUASI KEBIJAKAN BANTUAN LANGSUNG TUNAI DANA DESA BAGI WARGA MASYARAKAT MISKIN TERDAMPAK PANDEMI COVID- 19 DI DESA KETONGGO KECAMATAN BUNGKAL KABUPATEN PONOROGO TAHUN 2021 - Siti Asmonah; Joko Pramono; Aris Tri (JI@P, 2023)
This study aims to describe the evaluation of the The Policy of Direct CashAssistance Village Funds for the Poor Affected by the Covid-19 Pandemic inKetonggo Village, Bungkal District, Ponorogo Regency in 2021 based on thepolicy evaluation criteria proposed by William N Dunn, namely effectiveness,efficiency, adequacy, equity, responsiveness and appropriateness.This study usesa qualitative research method with a descriptive approach. Sources of data usedare people/informants and documents. Selection of informants using purposivesampling technique. Data collection techniques used are in-depth interviews anddocumentation.The results of this study indicate that (1) The Policy of DirectCash Assistance Village Funds in Ketonggo Village has been effective (2) ThePolicy of Direct Cash Assistance Village Funds in Ketonggo Village is quiteefficient but not maximal. (3) The Policy of Direct Cash Assistance Village Fundsin Ketonggo Village is good enough to overcome economic problems for the pooraffected by COVID-19. (4) The Policy of Direct Cash Assistance Village Funds inKetonggo Village has been implemented fairly and distributed evenly. (5) ThePolicy of Direct Cash Assistance Village Funds in Ketonggo Village satisfiesgroups of poor people. (6) The Policy of Direct Cash Assistance Village Funds inKetonggo Village is seen from the policy target, this policy has been right ontarget. Meanwhile, when viewed from the policy objectives, it has been achievedbut has not been maximized.Key words: effectiveness, efficiency, adequacy, equity, responsiveness andappropriatenes